The Influence of Leadership and Supervision Style on Teacher Performance (Case Study of Teachers at SMPN 18 Bandung City) - Widya Kusumah, Wida; Ridwan, S; Jusdijachlan, R (Greenation International Journal of Engineering Science, 2024)
The aim of this research is to describe leadership style, supervision and teacher performance and to test the magnitude of the influence of leadership style and supervision on teacher performance, both simultaneously and separately. The method used is a descriptive survey method and an explanatory survey. The type of investigation in this research is causality. The unit of analysis is teachers in SMPN 18 Bandung City with a sample of 44 people. The time horizon in this research is cross sectional and the analysis methods used are frequency distribution and path analysis. Based on the results of the research and discussion, it can be found that the Leadership Style in the SMPN 18 Bandung City environment is good, the supervision of teachers in the Bandung City SMPN 18 environment is good, the teachers at SMPN 18 Bandung City have high performance. Leadership style and supervision simultaneously influence teacher performance in the SMPN 18 Bandung City environment. However, partially, Leadership Style is more dominant in influencing teacher performance than supervision.